Performance Evaluation of Ag Doped TiO2 Nanoflowers in Dye-sensitized Solar Cell (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Many attempts have been made over the last few years to create effective visible light-activated photovoltaic using Titanium dioxide as photoanode materials in Dye-sensitized solar cell (DSSC). TiO2 possesses high photocatalytic behavior but has high charge recombination. In this study, the effect of introducing Ag dopant in TiO2 nanoflower morphology as a blocking layer to reduce charge recombination is investigated. The fabricated Ag doped TiO2 nanoflower was characterized using XRD, UV-Vis, IPCE, EIS analyses and Solar simulator under 1M solar illumination. Ag dopant may be considered a great approach to improving electron harvesting by suppressing electron recombination between the interface of TiO2 and electrolyte.